Experiment of precipitation-driven dynamic compaction technology in the treatment of silty clay sites: A case study of Yangluo project in Wuhan - Mingqing LAN (Shuiwen dizhi gongcheng dizhi)
Traditional soft foundation treatment methods often prove ineffective for muck clay soil foundations. This study investigated the reinforcement mechanism and construction process parameters of a novel dewatering-intensive tamping technique using the Yangluo project as a case study. The method integrated dynamic compaction with well-point dewatering, leveraging well-points to reduce excess pore water pressure generated by tamping while facilitating pore water discharge. During the Yangluo project, the groundwater level was lowered to 3 m below the ground surface within about 2 d before the first round of tamping, to 5 m within about 3 d before the second round of tamping, and to 5 m within about 6 d before the tamping, with the entire dewatering cycle of approximately 11 d. After the first round of tamping, the excess pore water pressure dissipated by 70% in about 7 d. The test results show that the dewatering-intensive tamping method can improve the consolidation of soft clay significantly in a short time, mitigates the “rubber soil” phenomenon, effectively treat the soil to a depth of 6.0 meters, and enhances the bearing capacity of the soft soil foundation (>150 kPa). This study establishes a theoretical foundation and practical construction parameters for the treatment of soft soil foundations, particularly in China’s coastal regions, where such conditions are prevalent.